Novel Strobilurin Derivatives Containing Carboxylate Unit as Potential Antifungal Agents - Bao, Longzhu; Wang, Shuangshuang; Song, Di; Wang, Jingjing; Yue, Xiali; Cao, Xiufang (Letters in Drug Design & Discovery, 2020)
Background: Due to the extensive use of a single fungicide to control crop diseases, the increase of resistant individuals leads to control failures. The search for molecules with fungicidal activity is still ongoing. Strobilurin is one of the most popularly used fungicides in the agrochemical field. A large number of strobilurin derivatives with both high activity and low toxicity have been developed. Methods: In the present study, a series of novel ortho-substituted benzyl carboxylates were efficiently synthesized by the reaction of (E)-methyl 2-(2-(bromom-ethyl)phenyl)-2-methox-yiminoaceta with various carboxylic acids. Their structures were confirmed and characterized by 1H NMR, 13C NMR, and ESI-MS analysis. Their fungicidal activities against common phytopathogenic fungi from six major cash crops were screened based on the pesticides guidelines for the laboratory bioactivity tests. Results: The primary fungicidal activity test results indicate that all compounds showed a certain inhibitory effect on the growth of 13 plants pathogenic fungi at a concentration of 100 ppm, and Compd. 3 has the most obvious inhibitory effect on all fungi. Further fungicidal activity studies indicate that some of these novel strobilurin derivatives containing carboxylate unit exhibited potential in vitro fungicidal activities at the dosage of 6.25 mg/L-1. Conclusion: A series of the ortho-substituted benzyl carboxylates derivatives containing β- methoxyacrylate moiety were designed and synthesized by modifying the side chain of traditional strobilurin fungicide. Compd. 3, Compd. 2 and Compd. 16 were identified as the most promising candidates for further study.
Keywords: carboxylate